Membrane Thickness as a Key Factor Contributing to the Activation of Osmosensors and Essential Ras Signaling Pathways - Cohen, B. Eleazar (Frontiers in Cell and Developmental Biology, 2018)
The cell membrane provides a functional link between the external environment and the replicating DNA genome by using ligand-gated receptors and chemical signals to activate signaling transduction pathways. However, increasing evidence has also indicated that the phospholipid bilayer itself by altering various physical parameters serves as a sensor that regulate membrane proteins in a specific manner. Thus, changes in thickness and/or curvature of the membrane induced by mechanical forces such as osmotic pressure can be transmitted through the transmembrane helices of protein sensors to activate MAP kinase signaling pathways that regulate cell growth. Local changes of membrane thickness exerted by anti-bacterial agents such as colistin, small amphiphilic peptides, or the anti-fungal antibiotic Amphotericin B can also lead to the triggering of signal transduction pathways from bacteria to mammalian cells. The present review underscores the foundational role that the adaptation of membrane proteins to the biophysical properties of the lipid bilayer has had on the function of cell signaling pathways from bacteria and fungi to mammalian cells.